Euskaraz idatziriko Asteteren dotrina bat - Ibarra Murillo, Orreaga (Huarte de San Juan. Filología y Didáctica de la Lengua, 2014)
This article publishes and analyses a doctrin of Astete, found in a rural house in Leitza (Navarre).The autor is unknown. Several doctrines circulated in there villages during the 19th century and they were all adapted to the different Basque dialects. Thanks to the analysis of its characteristics, we can claim that it presents some common features of the Baztan dialect. In all likehood, it was brought by a nun from this rural house born there. Althought it may not be very original, some features are worth being studied in greater depth from the dialectological point of view.
Keywords: Doctrine; Basque dialect; old text; Baztan dialect